Senegal : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper offers policy recommendations for Senegal to reach high and sustained growth with the goal of exiting low-income country status. For Senegal to reach Plan Senegal Emergent (PSE) objectives, reforms under the PSE need to create space for small and medium-sized enterprises and foreign direct investment to thrive. Reform of Senegal's business environment needs to be accelerated. Macrostructural reforms should be stepped up in the energy sector, in which Senegal still ranks 170th in the world. Progress in the electricity sector can be achieved by continuing to improve reliability of supply and reduce electricity costs. Reform of the taxation system, by simplifying procedures and optimizing the tax rates, is another macro-critical area in which Senegal needs to make significant strides.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet